Improving Learning Outcomes through the Problem Based Learning Model in Islamic Education Subjects in Elementary Schools - Muhammad Cholil Albab Cholil (FITK UIN Walisongo Semarang, 2025)
This research aims to improve the learning outcomes of grade IV students in the learning of Islamic Religious Education and Ethics, especially the material of Surah Al-Hujurat verse 13, through the application of the Problem Based Learning (PBL) learning model. This Class Action Research (PTK) is carried out in two cycles, each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 28 students at SD Negeri Balerejo 3, Dempet, Demak. Data collection is carried out through written tests, observation sheets, and documentation, then analyzed quantitatively and qualitatively to evaluate the improvement of student activities and learning outcomes. The results showed that the average score of students in the first cycle was 65 with a completeness of 36%, while in the second cycle it increased to 77 with a completeness of 89%. These findings prove that PBL is effective in improving learning outcomes, critical thinking skills, problem-solving skills, and student activeness during learning. The contribution of this research provides an alternative learning model that is effective in associating religious values with the context of daily life in Islamic Religious Education subjects